IMPLEMENTASI PASAL 35 PERATURAN DAERAH PROVINSI RIAU NOMOR 17 TAHUN 2018 TENTANG PENANGANAN FAKIR MISKIN DI KOTA PEKANBARU - PutriAna Patmala Lubis; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Poverty is a social problem that occurs in the Riau province that requires special handling and is a major and complex problem in social development that requires special attention from the local government. from year to year makes the requirements for getting a job stricter. The purpose of writing this thesis, firstly, is to find out how to implement Article 35 of the Riau Province Regional Regulation Number 17 of 2018 concerning Handling the Poor in Pekanbaru City, secondly, to find out what are the inhibiting factors in the implementation of Article 35 of the Riau Province Regional Regulation Number 17 of 2018 concerning Handling the Poor in Pekanbaru City. Third, to find out what efforts should be made by the Riau Provincial Government in Handling the Poor in Pekanbaru City. legal research used is the type of empirical or sociological research. This empirical or sociological legal research is research in the form of empirical studies to find theories regarding the working process of law in society. From the results of the study, there are three main things that can be concluded: First, how to implement Article 35 of the Regional Regulation of Riau Province Number 17 of 2018 concerning Handling the Poor in Pekanbaru City, Second, What are the Inhibiting Factors in the Implementation of Article 35 of the Regional Regulation of Riau Province Number 17 of 2018 regarding the Handling of the Poor in Pekanbaru City, Third What Efforts Should Be Done by the Riau Provincial Government through the Social Service in Handling the Poor in Pekanbaru City.Keyword: Implementation – Local Regulation – Handling The Poor